Assessing the potential impact of COVID-19 Omicron variant: Insight through a fractional piecewise model - Xiao-Ping Li; Mahmoud H. DarAssi; Muhammad Altaf Khan; C.W. Chukwu; Mohammad Y. Alshahrani; Mesfer Al Shahrani; Muhammad Bilal Riaz (Results in Physics, 2022)
We consider a new mathematical model for the COVID-19 disease with Omicron variant mutation. We formulate in details the modeling of the problem with omicron variant in classical differential equations. We use the definition of the Atangana–Baleanu derivative and obtain the extended fractional version of the omicron model. We study mathematical results for the fractional model and show the local asymptotical stability of the model for infection-free case if R0<1. We show the global asymptotically stable of the model for the disease free case when R0≤1. We show the existence and uniqueness of solution of the fractional model. We further extend the fractional order model into piecewise differential equation system and give a numerical algorithm for their numerical simulation. We consider the real cases of COVID-19 in South Africa of the third wave March 2021–Sep 2021 and estimate the model parameters and get R0≈1.4004. The real parameters values are used to show the graphical results for the fractional and piecewise model.